Ceftazidime-Avibactam Can Treat UTIs Caused by Multidrug-Resistant Enterobacteriaceae - Hoyle, Brian (MD Conference Express, 2015)
Resistance of multidrug resistant Gram-negative pathogens to carbapenems is increasing. The value of ceftazidime and avibactam as an alternative to carbapenems was explored in the REPRISE trial. The results indicate that the combination of ceftazidime and avibactam is tolerable and effective, with clinical success similar best available therapy (typically carbapenem monotherapy).